Issues of Defining Administrative and Tort Relations as an Object of Legal Research (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The concept of administrative and tort relations, their social nature, features (properties, characteristics), specific features as a type of administrative and legal relations, structure (objects, subjects and content) and types of administrative and tort relations have been characterized. The grounds for the origin, change and termination of administrative and tort relations, their separation from other similar relations have been highlighted.The author has distinguished three groups of subjects of administrative and tort relations. The first group of subjects are persons prosecuted for administrative torts. The second group includes the subjects of administrative and tort relations on the part of the state (agencies, officials). The third group of subjects includes all others (a victim, a lawyer, witnesses, etc.).The following stages of administrative and tort relations have been distinguished: initiation of the case, consideration and resolution of the case, execution of the decision (resolution) in the case, appeal and protesting the resolution.A number of characteristic features of administrative and tort relations inherent in other types of relations have been singled out. Administrative and tort relations have been compared with criminal and civil relations.The peculiarity of the subject composition of administrative and tort relations has been determined, based on the presence of a public administration authority and its officials as a subject of administrative jurisdiction. Specific features of administrative and tort relations have been distinguished.It has been determined that the structure of individual administrative and tort relations consists of subjects, object and content. Subjects of administrative and tort relations have been classified with the following types: 1) administrative offenders, as well as legal representatives of juvenile offenders; 2) officials authorized to use administrative coercion to prevent or terminate administrative offenses; 3) persons with administrative and jurisdictional powers; 4) persons who implement (perform) administrative penalties; 5) persons who are the third party in cases on administrative offenses.The author has raised the topical and debatable issue of the legal status of legal entities of private and public law within administrative and tort relations (in particular, their tort legal ability).Administrative and tort relations differ according to the subject that applies the norms of the Code of Ukraine on Administrative Offenses, i.e., based on the jurisdiction of cases of administrative offenses, the scope of administrative and tort relations, and depending on the stages and phases of proceedings on administrative offenses. It has been also noted that administrative and tort relations can be divided into property and non-property, material and procedural, those that occur within administrative procedure and those that occur within court procedure, etc.It has been concluded that there is a relatively separate area of relations – administrative and tort sphere among the variety of legal relations in Ukraine. Therefore, there is an objective need for the formation of administrative and tort law.
Keywords: administrative and legal relations; a tort; administrative and tort relations; offenses; administrative liability.